15=4.3n-2.1(n-4)

Simple and best practice solution for 15=4.3n-2.1(n-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15=4.3n-2.1(n-4) equation:


Simplifying
15 = 4.3n + -2.1(n + -4)

Reorder the terms:
15 = 4.3n + -2.1(-4 + n)
15 = 4.3n + (-4 * -2.1 + n * -2.1)
15 = 4.3n + (8.4 + -2.1n)

Reorder the terms:
15 = 8.4 + 4.3n + -2.1n

Combine like terms: 4.3n + -2.1n = 2.2n
15 = 8.4 + 2.2n

Solving
15 = 8.4 + 2.2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-2.2n' to each side of the equation.
15 + -2.2n = 8.4 + 2.2n + -2.2n

Combine like terms: 2.2n + -2.2n = 0.0
15 + -2.2n = 8.4 + 0.0
15 + -2.2n = 8.4

Add '-15' to each side of the equation.
15 + -15 + -2.2n = 8.4 + -15

Combine like terms: 15 + -15 = 0
0 + -2.2n = 8.4 + -15
-2.2n = 8.4 + -15

Combine like terms: 8.4 + -15 = -6.6
-2.2n = -6.6

Divide each side by '-2.2'.
n = 3

Simplifying
n = 3

 

See similar equations:

| 4(-2)-6m=-2 | | 4(x-3)=6(x+5) | | 4(0)-6m=-2 | | 4(2)-6m=-2 | | 10+6(-2)=12 | | 10m+6(-2)=12 | | 10m+6(-1)=12 | | 10m+6(0)=12 | | 2(a-4)=4a-a(2a+4) | | d=f+fx | | Y+2+3Y=-2+14 | | 4x+3-2x=-3-5+4x | | k-3k=6k+5-8k | | 2a-5=-3+3(a-2) | | 4k+m(-3)=-3 | | 2x-2+2x=4-8x+5x | | 3ab-2b(12)=12 | | 5+2(2x-1)=4(x+1) | | 4x+2-1=4-3+2x | | 2x+6=x+9 | | -23=2a-10-a | | 25(d-12)=4 | | 5(2x-3)=15 | | 2x+3=4x | | 4x-4=3x+6 | | 8(-3)-4y=-12 | | 2+X-5=-X+3-4X | | 8(-1)-4y=-12 | | -3x+9y=-18 | | 8(1)-4y=-12 | | 18=y-7 | | 6y=-3(-4)+12 | | 2x+3=5x | | 6y=-3(-2)+12 | | 4x-6-4=-3x+6+2 | | 6y=-3(0)+12 | | 2(x+9)=3(x-9) | | xp+yp=z | | -2=(n-8) | | -2+2x=5x-4 | | 3+4-5x=3x-1 | | 2x-3x+2=3+4 | | -8=-1(x-8) | | -3x+5=6x+2 | | 5x+34=-2(1-7x) | | 5-3x-2=4-3x-2 | | 5-3x-2=4-3x-2x | | 8x-2=-9+7x | | -9=7-5x | | 4x+3+6x=3x+2+8 | | 3-4x+4=6-5x-2 | | 3(2x-3)=7-x | | -2z-xy=x+7 | | -w+4(w+3)=-12 | | 9+-6-6t=6 | | 3+a-2=4-2a | | -23=-2a-10+8 | | 13-3d=-8 | | 5x+7=-7x+19 | | 2(8+4c)=32 | | 5(b+4)-6b=-24 | | (4-n)2.1-4.3n=15 | | 6-3d=5(2-d) | | 6x=9.6 | | 3v+8=8+2v+v |